Retornos anormais em fusões e aquisições: novas evidências do mercado brasileiro - Pinheiro, Amanda Freire Maia (2010)
The objective of this work is to analyze the abnormal returns of Mergers and Acquisitions (M&As) in Brazil and to verify if they can be explained by firm characteristics. This research provides contribution to the literature in two ways. First, it analyzes the longest period in the research of M&As in Brazil (1997-2009). Furthermore, this research analyzes the behavior of abnormal returns on M&As in different sub-periods, allowing to evaluate whether there have been changes over time. The results indicate that the abnormal returns of both firms are positive and statistically significant, and that the abnormal returns of acquired firms are larger than those of the acquirer firms. The results have changed over time. From 1997 to 2004, the abnormal returns of target firms are positive and the abnormal returns of acquirers are negative. However, from 2005 to 2009, the abnormal returns of both firms are positive. The target firms abnormal returns are positively related to the market value of both firms and negatively related to Tobin's Q and ROA of the acquirer. Moreover, in the most recent period, the abnormal returns of target firms are also positively related to their ROA and leverage.